Alsace and the French territorial debate: shifting the borders and discourses of regional and national identity - Eilderts, Luke L. (2019)
Keywords: dept.wll; faculty_collection; sabbatical_report

Morphological attrition - Schmitt, Elena (The Oxford Handbook of Language Attrition, 2019)
This volume is the first handbook dedicated to language attrition, the study of how a speaker's language may be affected by crosslinguistic interference and non-use. The effects of language attrition can be felt in all aspects of language knowledge, processing, and production, and can offer unique insights into the mind of bilingual language users. In this book, international experts in the field explore a comprehensive range of topics in language attrition, examining its theoretical implications, psycho- and neurolinguistic approaches, linguistic and extralinguistic factors, L2 attrition, and heritage languages. The chapters summarize current research and draw on insights from related fields such as child language development, language contact, language change, pathological developments, and second language acquisition.
Keywords: dept.wll; faculty_collection

Using the knowledge framework and genre pedagogy for technology-enhanced form-function project-based language learning - Gleason, Jesse; Link, Stephanie (Global perspectives on project-based language learning, teaching, and assessment: Key approaches, technology tools, and frameworks, 2019)
Keywords: dept.wll

Online teacher training using the knowledge framework and teaching-learning cycle for literacy development - Link, S; Gleason, Jesse (Social Practices in Higher Education: A Knowledge Framework Approach to Linguistic Research and Teaching, 2019)
Keywords: dept.wll; faculty_collection